Subjectivity of Implementation of Islamic Legal Thought Products - Muhammadong Muhammadong; Moatti Dylan; Sarkissian Catherine (P3M IAI Nusantara Batang Hari, 2023)
Among Muslims, applying the product of Islamic legal thought is the basic assumption in making decisions that can be used as a reference so that there is no need to take other legal products. Fiqh, fatwa, and jurisprudence are the basis for strengthening a decision so that Islamic society gets fair treatment. The product of mujtahid thinking is very subjective because there are no binding standard rules that are able to adjust the legal rules that have been formulated with the situation of society so that there is a great opportunity for change. The solution to overcoming this subjectivity needs to be made in a dictation so that it can be elaborated to find common points so that the products of Islamic legal thought can be accepted in society.